We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
48
3
avatar+45 

Can someone walk me throught this problem as an exeample. I do not understad this so far. The problem is:

 

Condense each expression into a single logarithim:

3*log102 + log10(x-4)

I woukd greatly apprcieate it if someone can help me out.

 Aug 29, 2019
 #1
avatar+103148 
+2

{We can ignore the subscript 10.......and write }

 

3*log2 + log(x-4)          {  a log b   =   log b ^a  }

 

log 2^3  + log (x - 4)       ( log a + log b  =   log (a * b)   }

 

log 8 + log (x - 4)   

 

  log ( 8 * (x - 4) )  =

 

log ( 8x - 32 )

 

 

cool cool cool    

 Aug 29, 2019
 #2
avatar+45 
+1

I got one more question:

 

How do I solve exponetial equations?

For example:

 

64x+7=45x-3

Masterx4020  Aug 29, 2019
 #3
avatar+103148 
+1

The trick is to try to get the bases the same

 

Note  64  =  4^3

 

So   we have

 

(4^3)^(x + 7)  =  (4)^(5x - 3)

 

4^(3x + 21)  = (4)^(5x - 3)       we  have the bases alike.....solve for the exponents

 

3x + 21  = 5x  - 3    

 

24  =  2x

 

x  = 12

 

 

cool cool cool

CPhill  Aug 29, 2019

27 Online Users

avatar